1999
DOI: 10.1007/bf02433389
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and function of placental macrophagesin vitro in different outcomes of pregnancy

Abstract: Antigenic phenotype and phagocytic activity of macrophages isolated from the placenta at different terms of gestation and different types of delivery were studied. The expression of MHC II and CR3 antigens and Fc-and C3-mediated phagocytosis increased during gestation. These parameters were increased during labor occurring in the second trimester, which indicates activation of placental macrophages in preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…C. Vince and P. Johnson [64] reported that uteroplacental macrophages are multipotent cells with a wide range of biological effects. Our experiments [2,3] and published data confirm the key role of FPM in the regulation of birth activity. Here we considered only one aspect of FPM functioning: their involvement in the cytokinemediated regulation of labor.…”
Section: Th2supporting
confidence: 92%
See 1 more Smart Citation
“…C. Vince and P. Johnson [64] reported that uteroplacental macrophages are multipotent cells with a wide range of biological effects. Our experiments [2,3] and published data confirm the key role of FPM in the regulation of birth activity. Here we considered only one aspect of FPM functioning: their involvement in the cytokinemediated regulation of labor.…”
Section: Th2supporting
confidence: 92%
“…The placenta and membranes responsible for the maintenance and normal development of the fetus are temporal structures, which can be studied only after labor. The models based on tissue and cell cultures are promising for studies of fetoplacental cells [1][2][3][31][32][33]58,62].…”
Section: Th2mentioning
confidence: 99%